Improving Mathematics Instruction for Early Childhood Teachers: Professional Development Components That Work - Varol, Filiz; Farran, Dale C.; Bilbrey, Carol; Vorhaus, Elizabeth A.; Hofer, Kerry Guess (My University, 2012)
The purpose of this study is to critically investigate the association between preschool teachers' mathematics instruction and their participation in a preschool mathematics intervention program in terms of 2 perspectives. First, the study examined whether preschool teachers' participation in the preschool mathematics intervention program had significant effects on implementing mathematical activities more often and with higher quality in their classrooms. Second, within the treatment group, the study examined the effects of exposure to professional development as well as individual contributions of various professional development types on the amount and quality of mathematics activities the teachers provided for their students. © 2012 Taylor and Francis Group, LLC.
Keywords: early childhood education; mathematics; preschool teachers; professional development